ANALYZING ILLOCUTIONARY ACTS OF NETIZEN COMMENTS IN FOOTBALL: RACISM-RELATED INSTAGRAM POST - Azzura, Danisya; Chan, Al Maghvirah (Program Studi Sastra Inggris, 2026)
This research analyzes the illocutionary acts of comments on Instagram directed towards soccer players, focusing on Vinicius Junior who posted about racism. The theories used in this research are Searle's (1979) illocutionary act types and Leech's (1983) illocutionary act functions. The purpose of this research is to identify and categorize comments based on their types and functions. The data consists of 201 English comments responding to Vinicius Junior's Instagram post on May 22, 2023, when he voiced his opposition to racism in soccer. The research results indicate that the expressive illocutionary act type is the most dominant (44.28%), followed by assertive (31.84%), directive (17.91%), and commissive (5.97%). No declarative illocutionary acts were found in the dataset. Additionally, the most frequently used illocutionary act function is the convivial function (57.71%), reflecting messages of support and moral encouragement, followed by the conflict function (28.36%), representing hate speech and racist comments, then the collaborative function (7.46%) and lastly the competitive function (6.47%). Expressive illocutionary acts include expressions of feelings such as like, sorrow, praise, and reproach.